Nikola Tesla - Fankhouser, Kris (Chicago, Illinois : World Book, Inc., 2018)
"A biography of the Serbian American inventor Nikola Tesla"--
1090L
Keywords: Tesla, Nikola, -- 1856-1943 -- Juvenile literature; Serbian American inventors -- Biography; Juvenile literature; Biographies